Dampak Kepuasan Kerja dan Kepemimpinan Transformasional Terhadap Organizational Citizenship Behavior di Lembaga Riset Perguruan Tinggi - Abdul Azis Apandi; Eny Nuryani; Taufiq Rahmat (Program Studi Manajemen, Universitas Al Ghifari, 2023)
Objective: This research aims to analyze the influence of job satisfaction and transformational leadership on organizational citizenship behavior (OCB) among employees at the Center for Development Dynamics Research, Universitas Padjadjaran.Methods: Quantitative method was used in this study, with a sample comprising all employees at the Center for Development Dynamics Research, Universitas Padjadjaran, totaling 46 respondents. Data were collected through a census using questionnaires, and the data were analyzed using multiple linear regression.Results: The results indicate a positive and significant simultaneous influence of job satisfaction and transformational leadership on organizational citizenship behavior. The variables of job satisfaction and transformational leadership together account for 71.9% of the variance in organizational citizenship behavior, while the remaining 28.1% can be attributed to other factors.Limitations: This research has several limitations, including a limited number of respondents and being conducted solely at the Center for Development Dynamics Research, Universitas Padjadjaran. Therefore, caution is needed when generalizing the results to other settings.Keywords: job satisfaction, transformational leadership, organizational citizenship behavior.